(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: The transrectal ultrasound (TRUS)-guided prostate biopsy protocols have been an optimizing strategy for diagnosis of prostate cancer. In this study, we aim to examine the cancer detection rate and the complications following prostate biopsy at Hoan My Cuu Long Hospital. Methods: We retrospectively reviewed medical data of patients who underwent TRUSguided prostate biopsy in 12/2016 to 08/2022 at our institution. The pathological outcomes, major complications were recorded and assessed clinically. Results: In this study, 129 patients who underwent TRUS-guided prostate biopsy were enrolled. The mean age was 73,33 years. The complications were infrequent, hematospermia in 13 patients (10.1%). Overall, 40 patients (31%) were diagnosed with prostate cancer. Conclutions: Our study demonstrated the cancer detection rate, and type of complications following TRUS-guided prostate biopsy.